(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
It attempts to reproduce the performance of one ormore human experts, most commonly in a specific problem domain, and is atraditional application and/or subfield of artificial intelligence. A widevariety of methods can be used to simulate the performance of the experthowever common to most or all are 1) the creation of a so-called"knowledge base" which uses some knowledge representation formalismto capture the subject matter experts (SME) knowledge and